Conceptions of school assessment: what do Finnish primary school students think of assessment? - Annuroosa Ammala; Outi Kyro-Ammala (University of Aberdeen, School of Education, 2018)
This article will describe a study that aimed to define Finnish primary students' conceptions of the purpose of school assessments. With the term 'school assessment', we refer to assessments that individual teachers employ as part of their pedagogy in order to evaluate students' learning processes on the basis of curriculum. We applied the phenomenographic method and gathered the data by interviewing 16 students (aged 10-13 years), from two different schools: a municipal primary school and a Steiner school. We analysed the data using a phenomenographic approach and formed vertical description categories. According to our study, students recognise the learning promoting, declaratory and external functions of assessment, which form the three description categories and the main results. They find that assessment promotes their learning, stating that it makes them commit to learning and that it guides and motivates them. Assessment also seems to have a declaratory purpose: the students expressed that it offers information about their knowledge level not only to them but also to their parents and teachers. The third description category is the external function of assessment, which arose when the students stated that assessment is helpful for their future working lives, to inform their future employers and schools about their skills and knowledge